RF plasma functionalization of exfoliated multi-layered graphene as cement reinforcement - Dela Vega, Ma. Shanlene D.C.; Vasquez, Magdaleno R. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Graphene has been termed as the "wonder material" catching the interest of researchers due to its remarkable electronic, optical, thermal, and mechanical properties that is being utilized in energy storage, sensors and electronics, coatings and barriers, and composite applications. Recent developments explore the use of graphene, being the strongest material ever measured, as cement reinforcement due to its high Young's modulus (1 TPa), high strength (130 GPa), and large total surface area while still being lightweight. The first part of this study delved on the exfoliation and functionalization of multi-layered graphene. Liquid phase exfoliation studies of < 20μm graphite particles revealed an optimum sonication time of 5 h in ethanol-water medium. Additional heat treatment of the exfoliated flakes decreased the number of graphene layers to 25 %, confirmed from Raman spectral and scanning electron microscopy (SEM) analyses. The exfoliated multi-layered graphene was spray-deposited on different glass substrates and functionalized using 13.56 MHz radio-frequency (RF) plasma system under argon (Ar) and oxygen (O2) environments. Optical emission spectral analyses of the discharge showed the presence of active O2 species which can functionalized the multi-layered graphene surface as revealed from the x-ray photoelectron spectroscopy. Contact angle measurements and surface free energy calculations showed an increase in hydrophilicity of the exfoliated multi-layered graphene thereby improving its dispersibility. Gram-scale production of functionalized multi-layered graphene was also developed in this study. Graphite particles were functionalized using the same RF plasma system and, subsequently, functionalized multi-layered graphene was produced via liquid-phase exfoliation. The exfoliated functionalized multi-layered graphene flakes were examined using scanning electron microscopy, atomic force microscopy, dynamic light scattering, ultraviolet-visible spectroscopy, Raman spectroscopy, and x-ray diffraction. The effect of functionalized multi-layered graphene (f-G) with varying concentrations as cement reinforcement was investiga ted by subjecting the functionalized multi-layered graphene-cement composites to a standard compression test. The compressive strength significantly increased by 4.65% and 56.07% upon the addition of 0.1 and 0.5 wt% f-G, respectively, after curing for 7 days. Similarly, the addition of 0.1 and 0.5 wt% f-G resulted to an increase of 18.85% and 55.88%, respectively, in the compressive strength after 28 days. These important results showed that the addition of small amounts of functionalized exfoliated multilayered graphene can significantly improve the compressive strength of cement.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Graphene; Cement